Biodegradable covering film containing sulfate minerals
By adding sulfate minerals, especially halolite, to the biodegradable plastic covering film, the problem of failure to completely decompose the covering in the prior art is solved, and a higher biodegradation rate and soil fertility improvement are achieved.
Patent Information
- Application Number
- CN202380061156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-28
- Filing Date
- 2023-08-25
- Publication Date
- 2025-04-29
AI Technical Summary
The existing biodegradable plastic coverings cannot be completely decomposed within a reasonable time, affecting their environmental friendliness and agricultural application efficiency.
The sulfate minerals at a concentration of 1% w/w-50% w/w, especially halide or a combination thereof, are added as additives to improve biodegradability and fertilizer function.
By adding sulfate minerals, the biodegradation rate of the covering film is increased to 10%-16% per year, and beneficial nutrients are released during the degradation process, promoting soil fertility and plant growth.
Smart Images

Figure CN119907623A_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to the field of plastics, and in particular to adding inorganic additives to agricultural covering films. Background of the Invention
[0003] Mulching is an agricultural technique that involves covering the soil with a specific film to protect crops and soil from atmospheric factors that can dry out the ground, spoil fruits, cool the soil and cause fertilizers to leach out, so mulching is necessary for plant growth. It also helps prevent the growth of weeds.
[0004] Moreover, mulching brings higher yields and makes crops mature earlier.Mulching is one of the most widespread agricultural techniques as its results are very satisfactory and the process does not involve great costs.
[0005] Low-density polyethylene (LDPE) is widely used in agriculture due to its mechanical and optical properties.
[0006] Biodegradable plastic mulches (BDMs) offer an environmentally sustainable alternative to conventional polyethylene (PE) mulches. Unlike PE films that need to be removed after use, BDMs are tilled into the soil where they are expected to biodegrade.
[0007] Bandopadhyay et al. (Front. Microbiol., April 26, 2018 | https: / / doi.org / 10.3389 / fmicb.2018.00819) discuss the fact that biodegradable plastic mulches (BDMs) have been developed as an alternative to PE mulch films and are designed to be cultivated into the soil after use, where resident microorganisms degrade the plastic. BDMs can be prepared from biobased polymers derived from microorganisms or plants or materials of fossil origin. Common biobased polymers used in BDMs include polylactic acid (PLA), starch, cellulose, and polyhydroxyalkanoates (PHA). Fossil-derived polyesters used in BDMs include poly(butylene succinate) (PBS), poly(butylene succinate-co-adipate) (PBSA), and poly(butylene adipate-co-terephthalate) (PBAT). The polymers used in BDMs contain ester bonds or are polysaccharides, which are susceptible to microbial hydrolysis. In theory, BDM should be completely decomposed by soil microorganisms and converted into microbial biomass, CO2, and water. In practice, complete decomposition within a reasonable amount of time is not always observed.
[0008] CN115926347A discloses a biodegradable covering film for slow release of fertilizers and a preparation method and application thereof.
[0009] CN111995462 discloses an environmentally friendly degradable fertilizer covering film.
[0010] KR20130075997 discloses a composition for a covering film and a biodegradable covering film having multifunctionality. SUMMARY OF THE INVENTION
[0012] According to some demonstrative embodiments, provided herein is a mulch film composition comprising a sulfate mineral (also referred to as sulfate) at a concentration between 1% w / w-50% w / w of the composition.
[0013] According to some demonstrative embodiments, the sulfate mineral may be selected from the group consisting of Anhydrite, Gypsum, Kieserite, Epsomite, Glauberite, Blodite, Langbeinite, Kainite, Schoenite, Polyhalite, or combinations thereof.
[0014] According to some demonstrative embodiments, the sulfate mineral may preferably be polyhalite or a combination of polyhalite and potash (KCl).
[0015] According to some embodiments, when discussing the combination of polyhalite and potash, a wide range of ratios may be useful, such as 10:90 to 90:10, but preferably, the ratio may be 50:50.
[0016] According to some demonstrative embodiments, the film may have a thickness of 7.5 mm to 150 mm, preferably 7.5 microns to 40 microns, most preferably 10 mm to 30 mm.
[0017] According to some demonstrative embodiments, the concentration of sulfate mineral may be 5% w / w-30% w / w, preferably 10% w / w-20% w / w of the composition.
[0018] According to some demonstrative embodiments, the cover film may be a biodegradable copolyester film.
[0019] According to some illustrative embodiments, provided herein is a process for producing a mulch film composition, the process comprising mixing 50%-99% of a biodegradable copolyester film with 1%-50% of polyhalite in an extruder at a temperature of 180° C.-240° C. and an RPM between 600-1000; extruding the mixture of the biodegradable copolyester film and polyhalite until brown pellets are produced; and transferring the brown pellets to a film extruder to produce a mulch film composition.
[0020] According to some demonstrative embodiments, the cover film composition may have a thickness between 7.5 microns and 40 microns.
[0021] According to some demonstrative embodiments, the extruder may be an 18 mm twin screw extruder.
[0022] According to some demonstrative embodiments, the cover film may also include plasticizers, stabilizers, pigment compounds, flame retardants, or reinforcing fillers.
[0023] According to some demonstrative embodiments, provided herein is a method for controlling biodegradation of a biodegradable mulch film, the method comprising incorporating into the film at least one sulfate mineral at a concentration of 10% w / w to 30% w / w.
[0024] According to some demonstrative embodiments, the at least one sulfate mineral may preferably be polyhalite or a combination of polyhalite and potash.
[0025] According to some demonstrative embodiments, controlling the biodegradation of the biodegradable cover film may include slowing the degradation rate of the film to 10%-16% per year. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Depicted is a graph showing biodegradation rate expressed as total cumulative CO2 released (mg), according to some demonstrative embodiments.
[0028] Figure 2 Depicted are photographs of cover film disintegration, according to some demonstrative embodiments.
[0029] Figure 3-Figure 9 Graph depicting biodegradation of films according to some embodiments of the present invention.
[0030] Fig.10 Photographs depicting disintegration of a cover film, according to some demonstrative embodiments. DETAILED DESCRIPTION OF THE INVENTION
[0032] According to some embodiments, provided herein are overburden film compositions comprising at least one sulfate mineral.
[0033] According to some embodiments, the mulch film compositions of the present invention may be degradable and / or biodegradable.
[0034] According to some embodiments, the term "degradable" may refer to the ability of the composition of the present invention to chemically degrade.
[0035] According to some embodiments, the term "biodegradable" may refer to the ability of the composition of the present invention to be broken down by bacteria and / or other living organisms.
[0036] According to some embodiments, the term "sulfate mineral" may include any suitable mineral selected from the group consisting of kieserite, epsomite, glauberite, leonite, leonite, philadelphite, kainite, polyhalite, or combinations thereof.
[0037] According to some embodiments, the term "mulch film composition" as used herein may refer to any suitable film for covering the soil to protect crops and soil from being contaminated by atmospheric factors, which may dry the ground, spoil fruits, cool the soil, and cause fertilizers to run off, and also to prevent weed growth.
[0038] According to some embodiments, the cover film may preferably include one or more films selected from the group consisting of a copolyester film, a low-density polyethylene (LDPE) film, a polylactic acid (PLA) film, and the like.
[0039] According to some demonstrative embodiments, when left on the ground, the mulch films of the present invention may dissolve and undergo a degradation or biodegradation process.
[0040] According to some embodiments, in order to produce the cover film of the present invention, some additives can be added during the production process, for example, in order to impart specific properties. These additives can include materials such as plasticizers, stabilizers, pigment compounds, flame retardants, reinforcing fillers and the like.
[0041] According to some embodiments, the coverings of the present invention may include fillers, for example, to increase impact resistance, fatigue resistance, creep resistance, and / or to reduce cost.
[0042] According to some embodiments, the filler may be selected from the group consisting of calcium carbonate, talc, clay, zinc metal powder, wood flour, barium sulfate, sodium sulfate, and phosphogypsum.
[0043] According to some embodiments, barium sulfate, sodium sulfate, and phosphogypsum may be preferred fillers, for example, in terms of increasing impact resistance, fatigue resistance, creep resistance, and reducing cost.
[0044] According to some embodiments, after the mulch film of the present invention degrades, sulfate minerals may be released to the ground and fertilize the soil.
[0045] According to some demonstrative embodiments, the specific use of sulfate minerals such as polyhalite allows for controlled biodegradation of the cover films of the present invention.
[0046] According to some embodiments, the unique use of polyhalite may allow for faster biodegradation of the cover film, as explained in detail below.
[0047] According to some illustrative embodiments, the sulfate mineral may preferably be kieserite or polyhalite.
[0048] According to some embodiments, due to its unique crystal structure and solubility, polyhalite may be particularly useful when included in a cover film, preferably in a biodegradable copolyester, so that the entire cover film biodegrades faster than the cover alone, as will be seen below.
[0049] According to some embodiments, polyhalite, being a mined, non-ductile material, is challenging to incorporate into overburden films.
[0050] However, according to some embodiments, particularly when a biodegradable copolyester film is used, the copolyester may be heated to a temperature of 160°C-240°C, preferably 170°C-230°C, most preferably 180°C-220°C, and therefore, most fertilizers will not be able to maintain their structure and morphology and will most likely melt or deform.
[0051] Polyhalite, unlike many other fertilizers such as urea, may lose some water content when exposed to the high temperatures mentioned above, but it will not melt or deform and is much more stable than other common fertilizers.
[0052] Furthermore, since polyhalite is generally colorless, white, brown, or gray, it also tends to blend with the overlay film to produce a film that is substantially uniform in appearance.
[0053] According to some embodiments, in order to grow properly, plants require nutrients that can usually be found in soil (nitrogen, potassium, calcium, zinc, magnesium, iron, manganese, etc.). Fertilizers are sometimes needed to achieve desired plant growth because these fertilizers can enhance the growth of plants.
[0054] This growth of plants is met in two ways, the traditional way is to provide nutrients additives. Some fertilizers work in a second mode by improving the water retention and aeration of the soil to enhance the effectiveness of the soil. Fertilizers usually provide three major macronutrients in varying proportions:
[0055] Nitrogen (N): leaf growth;
[0056] Phosphorus (P): Development of roots, flowers, seeds, and fruits;
[0057] Potassium (K): strong stem growth, water movement in plants,
[0058] Promote flowering and fruiting;
[0059] Three minor macronutrients: calcium (Ca), magnesium (Mg) and sulfur (S); micronutrients: copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), zinc (Zn), boron (B), and the occasional important presence of silicon (Si), cobalt (Cv) and vanadium (V) plus rare mineral catalysts.
[0060] The most reliable and effective way to align nutrient availability with plant needs is to control the release of nutrients into the soil solution through the use of slow release fertilizers or controlled release fertilizers.
[0061] Polyhalite is an evaporite mineral that is a hydrated sulfate of potassium, calcium, and magnesium with the formula: K2Ca2Mg(SO4)42H2O. Polyhalite is used as a fertilizer because it contains four important nutrients and is low in chlorides:
[0062] 48% SO3, as sulfate
[0063] 14% K2O
[0064] 6% MgO
[0065] 17% CaO.
[0066] According to some embodiments, during the production of the mulch film compositions of the present invention, one or more sulfate minerals, such as polyhalite, may be added to the polymerization process to produce a plastic.
[0067] According to some embodiments, adding polyhalite to the production process of the mulch film of the present invention can allow the polyhalite to be released when the mulch film degrades and provide a variety of beneficial effects, including, for example, dissolution of the mulch film, and enriching the ground with minerals and substances necessary for plant growth, and the like.
[0068] According to some embodiments, polyhalite exhibits slightly soluble properties and is virtually insoluble. Thus, when placed on soil, polyhalite allows for continued exposure of nutrients at the surface.
[0069] According to some embodiments, the presence of polyhalite in the ground can cause surrounding bacteria to proliferate and thrive from the unique combination of nutrients present in the polyhalite mineral.
[0070] According to some embodiments, such surrounding bacteria may allow for desirable degradation of cover films such as PLA films or copolyesters.
[0071] According to some embodiments, the term "desirable degradation" may refer to controlled degradation and / or complete degradation of the film, for example, leaving little or no residue.
[0072] According to some embodiments, conventional cover films may have a degradation rate of 5%-8.5% per year, while cover films comprising polyhalite may exhibit a degradation of 10%-16% per year.
[0073] According to some demonstrative embodiments, a common method of enhancing the biodegradability of mulch films may include the inclusion of additives such as starch, etc. According to some embodiments, the use of sulfates and particularly polyhalite, either alone or in combination with other fertilizers such as potash, may allow for the desired degradation of mulch films without the need for any such additives that promote biodegradation.
[0074] According to some embodiments, polyhalite is considered an organic fertilizer, unlike other fertilizers, such as urea, which undergo chemical processing.
[0075] According to some embodiments, specific uses of sulfates allow for beneficial results including fertilization of the ground beneath and around where the mulch is placed, the sulfates acting as fillers, and the sulfates enhancing or accelerating biodegradation of the mulch.
[0076] According to some embodiments, sulfates such as polyhalite or kieserite used in the mulch can gradually absorb moisture and indirectly enhance the penetration of moisture into the mulch, thereby accelerating the dissolution process. In addition, according to some embodiments, the sulfates can dissolve faster than the mulch, thereby creating voids in the mulch and expanding the surface area of the mulch during the biodegradation process.
[0077] According to some embodiments, the sulfate may preferably be polyhalite, since polyhalite is a naturally occurring mineral that has a low chloride content and therefore does not contribute to the salinity of the soil when released from a mulch, as compared to, for example, KCl or other fertilizers.
[0078] According to some demonstrative embodiments, the concentration of sulfate salts, such as polyhalite, in the overburden may be at least 5%, preferably at least 10%, and most preferably 10% w / w-30% w / w.
[0079] According to some embodiments, the thickness of the cover film composition of the present invention may be between 5 microns and 150 microns, preferably between 7.5 microns and 40 microns, and most preferably between 10 microns and 30 microns.
[0080] According to some embodiments, the use of greater than 5% w / w (let alone greater than 10% w / w) sulfate in the mulch provides unique and surprising benefits with minimal impact on the strength of the mulch.
[0081] While in most cases the substances are incorporated into the mulch in dilute amounts of 1% w / w-5% w / w, according to some embodiments, the ability to use relatively high concentrations such as 10% w / w, 20% w / w or even 30% w / w and more of sulfates such as polyhalite is a unique feature of the present invention, achieving both the beneficial effects of a fertilizer on the soil and the beneficial effects of controlled biodegradation of the mulch, but with surprisingly minimal impact on the strength of the mulch.
[0082] According to some embodiments, other additives can play an important role in the production process because they can be used to improve the cover film polymer properties. According to some embodiments, these additives can include, but are not limited to, plasticizers, stabilizers, antioxidants, thermal stabilizers, slip agents, flame retardants, heat stabilizers, pigments, reinforcing agents, and fillers.
[0083] According to some illustrative embodiments of the present invention, inorganic compounds may be used as additives, such as flame retardants, e.g., halogens or phosphate bases; stabilizers, e.g., lead-cadmium compounds; colorants, such as zinc, iron, cadmium, manganese compounds, titanium dioxide, and the like; fillers, such as calcium carbonate, talc, clay, zinc oxide, wood, barium sulfate, glass, and the like; and reinforcing compounds, such as glass fibers, carbon fibers, and the like.
[0084] The migration of inorganic additives, especially heavy metal based additives, and their release to the environment (e.g. when plastics are discarded) has been extensively studied. It is inferred that the release of many such additives may be harmful to the environment.
[0085] According to some demonstrative embodiments, provided herein is a method for controlling biodegradation of a biodegradable mulch film, the method comprising incorporating into the film at least one sulfate salt at a concentration of 10% w / w to 30% w / w.
[0086] According to some embodiments, the at least one sulfate salt may preferably be polyhalite, and according to some other embodiments, the polyhalite may be combined with potash, preferably in a 1:1 ratio with potash.
[0087] According to some embodiments, controlling the biodegradation of the biodegradable mulch film may include slowing the degradation rate of the film to 10%-16% per year, while the sulfate-free mulch film biodegrades at a rate of 5%-8.5% per year.
[0088] While the invention has been described with respect to a limited number of embodiments, it will be appreciated that many variations, modifications and other applications of the invention may be made.
[0089] It will be understood that, for the sake of clarity, the various features of the present invention described in the context of a separate embodiment may also be provided in combination in a single embodiment. On the contrary, for the sake of brevity, the various features of the present invention described in the context of a single embodiment may also be provided individually or in any suitable sub-combination. It will also be understood by those skilled in the art that the present invention is not limited by what has been particularly shown and described above. Example
[0090] Example 1
[0091] The goal of this work was to produce 30-micron membranes containing large amounts of polyhalite, a fertilizer additive.
[0092] The work was carried out in two stages, the first stage using low density polyethylene (LDPE) (e.g., LF2103 ex. SASOL) and the second stage using biodegradable compounds for agricultural films (any suitable compostable and mainly bio-based polymers for film applications can be used, e.g., M2351ex.BASF).
[0093] Results: Both masterbatches based on LDPE and biodegradable copolyester containing 50% polyhalite were prepared via Coperion twin screw extruder without any major problems. 30 micron LDPE films were produced up to a limit of 20% polyhalite and 30 micron biodegradable copolyester films were produced up to 30% polyhalite without any major problems. Processing was easier with biodegradable copolyester due to its elastomeric nature. The dispersion of polyhalite in both films was good.
[0094] Material:
[0095]
[0096] Table 1
[0097] First stage: LDPE (LF2103X ex SASOL)
[0098] Phase 1: Masterbatch production
[0099] Composition: 50% LDPE carrier (LF2103 ex. SASOL) and 50% polyhalite.
[0100] MB unit LDPE LF2103 % 49.0 Polyhalite % 50.0 Calcium stearate % 1.0 total % 100.0
[0101] Table 2
[0102] Machine: COPERION 18mm twin screw extruder.
[0103] Processing temperature: 180℃-240℃.
[0104] ·RPM:800.
[0105] Appearance: Brown pellets.
[0106] Phase 2: Membrane production
[0107] Composition: 2.5%-20% Polyhalite:
[0108]
[0109] Table 3
[0110] Machine: LF-400 blown film extruder.
[0111] Thickness: 30 microns - 40 microns
[0112] Processing temperature: 180℃-220℃.
[0113] ·RPM:90.
[0114] result:
[0115] 30 micron LDPE films were produced up to a limit of 20% polyhalite. The dispersion of polyhalite in the film was good.
[0116] Example 2
[0117] Production of biodegradable mulch films
[0118] Phase 1: Masterbatch production Composition: 50% M2351 carrier (biodegradable copolyester film) and 50% polyhalite
[0119] MB unit 50% Biodegradable copolyester film % 49.0 Polyhalite % 50.0 Calcium stearate % 1.0 total % 100.0
[0120] Table 4
[0121] Machine: COPERION 18mm twin screw extruder.
[0122] Processing temperature: 180℃-240℃.
[0123] ·RPM:800.
[0124] Appearance: Brown pellets.
[0125] Phase 2: Membrane production
[0126] Composition: 2.5%-30% Polyhalite:
[0127]
[0128] Table 5
[0129] Machine: LF-400 blown film extruder.
[0130] Thickness: 30 microns - 40 microns
[0131] Processing temperature: 180℃-220℃.
[0132] ·RPM:90.
[0133] result:
[0134] 30 micron biodegradable copolyester film (e.g. M2351) was produced up to 30% polyhalite without any problems. Processing was easier with the biodegradable copolyester film due to its elastic nature. The dispersion of polyhalite in the film was very good.
[0135] Example 3
[0136] Masterbatch production example
[0137] In the first stage, a LDPE masterbatch with polyhalite is produced. The ratio between LDPE and polyhalite is 1:1 (50% LDPE and 50% polyhalite)
[0138] The second stage consisted of adding pellets of LDPE to the batch until the polyhalite concentration was 30% w / w.
[0139] Example 4
[0140] Various samples of cover film were tested, the samples comprising: MB (masterbatch, blank-Ecoview M (biodegradable polymer of BASF, without polyhalite) (sample-1), sample containing 10% polyhalite (sample-2), sample containing 20% polyhalite (sample-3) and sample containing 30% polyhalite (sample-4).
[0141] As part of FprEN 17033:2017 Plastics – Biodegradable mulch films for agricultural and horticultural use – Requirements and test methods, samples were delivered as pellets for biodegradation testing and as films for disintegration.
[0142] Samples of the pellets were ground by cryogenic freezing mill.
[0143] The ground material was sieved to a size of 300-400 μm. We placed 4 grams of ground material in duplicate into bioreactors for biodegradation testing. The reference material was cellulose powder, also in duplicate (4 grams in each container).
[0144] The test system consisted of 12 2-liter batch bioreactor containers filled with 200 grams of compost extract and vermiculite (as inoculum). All bioreactors were in an incubator under a controlled environment of 25±2°C. The containers contained:
[0145] 2 blank containers with compost extract and vermiculite only.
[0146] 2 reference containers with compost extract and vermiculite + cellulose
[0147] 2 test containers to hold compost extract and vermiculite + mulch No. 1
[0148] 2 test containers for compost extract and vermiculite + mulch No. 2
[0149] 2 test containers to hold compost extract and vermiculite + mulch No. 3
[0150] 2 test containers holding compost extract and vermiculite + mulch No. 4.
[0151] Purpose of the test
[0152] 1. Study on the biodegradability of mulches with and without polyhalite in compost + vermiculite.
[0153] 2. Study on the disintegration of mulch films with polyhalite and mulch films without polyhalite in soil.
[0154] Experimental Procedure
[0155] The system was conducted according to the following: ISO 17556 procedure “Plastics – Determination of ultimate aerobic biodegradability in soil by measurement of oxygen demand or carbon dioxide released in a respirometer”, and FprEN 17033:2017 Plastics – Biodegradable mulch films for agricultural and horticultural use – Requirements and test methods.
[0156] CO2 was collected and analyzed in 1% NaOH solution.
[0157] Experimental setup test
[0158]
[0159] Table 6
[0160] result
[0161] Biodegradation in compost:
[0162] Time (day) blank Cellulose Polymer 1 Polymer 2 Polymer 3 Polymer 4 0 0 0 0 0 0 0 7 22.65 63.4 42.85 41.3 41.3 43.625 14 45.35 146.65 92.05 95.2 95.2 112.325 21 67.1 256.35 138.35 157.05 157.05 168.325 28 93.4 403.6 185.15 212.55 212.55 226.225 35 119 965 231 263 263 268.8
[0163] Table 7: Biodegradation expressed as total cumulative CO2 released (mg)
[0164] Example 5
[0165] The samples of covers were produced and contained: MB [Masterbatch, Blank-Ecovio M-BASF (a biodegradable copolyester film) 0% Polyhalite, Sample-1], 10% Polyhalite (Sample-2), 20% Polyhalite (Sample-3), 30% Polyhalite (Sample-4).
[0166] As part of FprEN 17033:2017 Plastics – Biodegradable mulch films for agricultural and horticultural use – Requirements and test methods, samples were delivered as pellets for biodegradation testing and as films for disintegration.
[0167] A sample of the pellet was ground in a cryogenic cryomill.
[0168] The ground material was sieved to a size of 300-400 μm. We placed 4 grams of ground material in duplicate into bioreactors for biodegradation testing. The reference material was cellulose powder, also in duplicate (4 grams in each container).
[0169] The test system consisted of 12 2-liter batch bioreactor containers filled with 200 grams of compost extract and vermiculite (as inoculum). All bioreactors were in an incubator under a controlled environment of 25±2°C. The containers contained:
[0170] 2 blank containers with compost extract and vermiculite only.
[0171] 2 reference containers with compost extract and vermiculite + cellulose
[0172] 2 test containers to hold compost extract and vermiculite + mulch No. 1
[0173] 2 test containers for compost extract and vermiculite + mulch No. 2
[0174] 2 test containers to hold compost extract and vermiculite + mulch No. 3
[0175] 2 test containers holding compost extract and vermiculite + mulch No. 4.
[0176] Purpose
[0177] 1. Study on the biodegradability of mulches with and without polyhalite in compost + vermiculite.
[0178] 2. Study on the disintegration of mulch films with polyhalite and mulch films without polyhalite in soil.
[0179] Experimental Procedure
[0180] The system was conducted according to the following: ISO 17556 procedure “Plastics – Determination of ultimate aerobic biodegradability in soil by measurement of oxygen demand or carbon dioxide released in a respirometer”, and FprEN 17033:2017 Plastics – Biodegradable mulch films for agricultural and horticultural use – Requirements and test methods.
[0181] CO2 was collected and analyzed in 1% NaOH solution.
[0182] Experimental setup test
[0183]
[0184] Table 8
[0185] result
[0186] 1. Biodegradation in composting:
[0187] Time (day) blank Cellulose Polymer 1 Polymer 2 Polymer 3 Polymer 4 0 0 0 0 0 0 0 7 23 63 43 41 41 44 14 45 147 92 95 95 112 21 67 256 138 157 157 168 28 93 404 185 213 213 226 35 119 965 231 263 263 269 42 143 1145 268 305 307 329 49 165 1297 302 354 355 390 56 195 1389 329 391 378 429 63 203 1493 350 418 403 460 70 211 1558 367 438 427 483 77 222 1637 390 464 454 511 84 245 1733 413 487 479 535 91 253 1853 429 505 498 554
[0188] Table 9: Biodegradation expressed as total cumulative CO2 released (mg)
[0189]
[0190] Table 10: Biodegradation % (calculated based on ThCO2, in grams of CO2 / gram of test material)
[0191] After 91 days, differences in biodegradation between the mulch films emerged. Of the 4 films tested, the film containing only MB and no polyhalite had the lowest biodegradation rate, and the film containing 30% polyhalite had the highest biodegradation curve. The film containing 30% polyhalite showed 5% degradation within 90 days, and the other compositions containing polyhalite (10% and 20%) showed between 3%-4% biodegradation within 90 days.
[0192] Cellulose (reference material according to ISO 17556) showed 27% degradation after 8 weeks.
[0193] Example 6 - Long-term biodegradability of mulch
[0194] Samples of coverings were produced and contained: MB (Masterbatch, Blank-Ecovio M-BASF 0% Polyhalite, Sample-1), 10% Polyhalite (Sample-2), 20% Polyhalite (Sample-3), 30% Polyhalite (Sample-4). (Samples are also referred to herein as polymers, e.g., Sample 1 corresponds to Polymer 1, etc.).
[0195] As part of FprEN 17033:2017 Plastics – Biodegradable mulch films for agricultural and horticultural purposes – Requirements and test methods, samples are delivered as pellets for biodegradation testing (ISO 17556) and as films for disintegration.
[0196] A sample of the pellet was ground in a cryogenic cryomill.
[0197] The ground material was sieved to a size of 300-400 μm. We placed 4 grams of ground material in duplicate into bioreactors for biodegradation testing. The reference material was cellulose powder, also in duplicate (4 grams in each container).
[0198] The test system consisted of 12 2-liter batch bioreactor vessels filled with 200 grams of compost extract and vermiculite as inoculum. All bioreactors were in an incubator under a controlled environment of 25±2°C.
[0199] 2 blank containers with compost extract and vermiculite only.
[0200] 2 reference containers with compost extract and vermiculite + cellulose
[0201] 2 test containers containing compost extract and vermiculite + mulch No. 1 (0%) - Sample 1
[0202] 2 test containers containing compost extract and vermiculite + mulch No. 2 (10%) - Sample 2
[0203] 2 test containers containing compost extract and vermiculite + mulch No. 3 (20%) - Sample 3
[0204] 2 test containers containing compost extract and vermiculite + mulch No. 4 (30%) - Sample 4.
[0205] Three containers containing standard soil from Germany were prepared according to ISO standard 17033.
[0206] Four samples of each mulch sheet (0%, 10%, 20% and 30%) were placed in a glass slide frame in the soil in each container.
[0207] The sheets were observed once a week for the first two months and every 2 weeks thereafter.
[0208] The mulch biodegradation results (CO2 accumulation) are presented in Table 11 below and in Figure 7-10 Described in:
[0209]
[0210] Table 11: Biodegradation of mulches (CO2 accumulation)
[0211] From the data presented herein, we can see that after 9 months we had 64% biodegradation of cellulose and 7%-13% biodegradation of mulches containing 0%-30% polyhalite.
[0212] The mulch containing 30% polyhalite exhibited 12.7% degradation, and the mulch containing 10%-20% polyhalite exhibited 6%-9% degradation.
[0213] After 9 months of testing in soil, partial disintegration of the mulch containing 20% polyhalite and the mulch containing 30% polyhalite was observed.
[0214] Reference now Figure 1 , Figure 1 A graph showing the biodegradation rate expressed as total cumulative CO2 released (mg) is depicted.
[0215] from Figure 1 As can be seen in Figure 3, after the first month, small differences in biodegradation between the cover films emerged. Of the 4 membranes tested, the membrane containing only MB and no polyhalite had the lowest biodegradation rate.
[0216] refer to Figure 2 , Figure 2 Photographs depicting the disintegration of the covering film.
[0217] Figure 2 A depicts photo Pic 1 taken at the end of the first week of cover disintegration testing (2021.11.25).
[0218] Figure 2 B depicts photo Pic 2 taken at the end of the first week of the cover disintegration test (2021.11.25).
[0219] Figure 2 C depicts photo Pic 1 taken at the end of the second week of the cover disintegration test (2021.1.12).
[0220] Figure 2 D depicts Photo 2 taken at the end of the second week of the cover disintegration test (2021.1.12).
[0221] Figure 2 E depicts Pic 5 taken at the end of eight weeks of cover disintegration testing (2022.1.25).
[0222] Figure 2 F depicts photo Pic 6 taken at the end of eight weeks of cover disintegration testing (2022.1.25).
[0223] According to some embodiments, it is apparent that no disintegration was noted after 2 weeks of testing, however, the covering with 30% polyhalite showed changes and disintegration after 8 weeks.
[0224] refer to Figure 3 , Figure 3 A graph showing % biodegradation (calculated based on ThCO2, in grams CO2 / gram test material, Polymer 1 - Polymer 4 relative to cellulose) is depicted.
[0225] refer to Figure 4 , Figure 4 A graph showing % Biodegradation (% Biodegradation of Polymer 1 - Polymer 4) is depicted.
[0226] refer to Figure 5 , Figure 5 A graph showing biodegradation (Polymer 1 - Polymer 4 relative to cellulose) as cumulative CO2 (mg) is depicted.
[0227] refer to Figure 6 , Figure 6 A graph showing biodegradation (Polymer 1 - Polymer 4) as cumulative CO2 (mg) is depicted.
[0228] refer to Figure 7 , Figure 7 Depicted are graphs showing mulch biodegradation of various mulch samples compared to cellulose and a blank over 280 days, according to some demonstrative embodiments.
[0229] from Figure 7 It can be seen that the samples containing cellulose exhibited the most extensive degradation, while covers containing varying concentrations of polyhalite showed more controlled degradation rates.
[0230] According to some embodiments, upon comparison, it is apparent that the covering comprising 30% w / w polyhalite exhibited the highest degree of degradation over time compared to 0% w / w, 10% w / w, or 20% w / w polyhalite content in the other samples.
[0231] According to some embodiments, it is apparent that various concentrations of polyhalite aid in the biodegradation of the mulch.
[0232] refer to Figure 8 , Figure 8 Depicted is a graph showing mulch biodegradation (in %) for various mulch samples over 280 days, without comparison to cellulose, according to some demonstrative embodiments.
[0233] from Figure 8It can be seen that the overlay membranes containing 10%, 20% or 30% polyhalite have a significant contribution to the biodegradability of the membrane compared to 0% polyhalite (30% polyhalite is about 12.7% biodegraded, 20% polyhalite is about 8% biodegraded, and 10% polyhalite is about 6.35% biodegraded).
[0234] According to some embodiments, conventional cover films may have a degradation rate of 5%-8.5% per year, while cover films comprising polyhalite may exhibit a degradation of 10%-16% per year.
[0235] refer to Fig. 9 , Fig. 9 Depicted are graphs showing mulch biodegradation of various mulch samples compared to cellulose and not compared to a blank over 280 days, according to some demonstrative embodiments.
[0236] refer to Fig.10 , Fig.10 Photographs depicting the disintegration of mulch films 34 weeks from creation and incorporation into soil.
[0237] 10A - Sample 1 - Mulch placed in soil for 34 weeks, containing 0% w / w polyhalite.
[0238] 10B - Sample 2 - Mulch placed in soil for 34 weeks, containing 10% w / w polyhalite.
[0239] 1OC - Sample 3 - Mulch placed in soil for 34 weeks, containing 20% w / w polyhalite.
[0240] 10D - Sample 4 - Mulch placed in soil for 34 weeks, containing 30% w / w polyhalite.
[0241] from Fig.10 It can be seen that even after 34 weeks, the mulch films containing different concentrations of polyhalite exhibited integrity, indicating that mulch strength persisted despite the relatively high amount of polyhalite in the mulch.
[0242] While the invention has been described with respect to a limited number of embodiments, it will be appreciated that many variations, modifications and other applications of the invention may be made.
[0243] Example 7
[0244] The test of Example 7 includes:
[0245] - Production of biodegradable mulches (also referred to as "biodegradable copolyesters" or "compostable polymer carriers") using polyhalite.
[0246] - Production of biodegradable mulch by addition of polyhalite / KCl.
[0247] Biodegradable compounds
[0248] Phase 1: Masterbatch production
[0249] Composition: 80% biodegradable copolyester film, also known as compostable polymer carrier (e.g. M2351); and 20% polyhalite, polyhalite / KCl.
[0250] JR-5791 Polyhalite Polyhalite+KCl 2507.43 unit 1 2 Compostable polymers % 79.5 79.5 fertilizer % 20.0 20.0 Calcium stearate % 0.5 0.5 total % 100.0 100.0
[0251] Table 12
[0252] Machine: COPERION 18mm twin screw extruder.
[0253] Processing temperature: 190℃-210℃.
[0254] ·RPM:750.
[0255] Appearance: Grey granules.
[0256] Phase 2: Film (covering) production
[0257] Composition: 10%, 20% polyhalite, polyhalite / KCl:
[0258]
[0259] Table 13
[0260] Machine: LF-400 blown film extruder.
[0261] Thickness: 20 microns - 30 microns
[0262] Processing temperature: 180℃-190℃.
[0263] ·RPM:90.
[0264] result:
[0265] -Polyhalite:
[0266] Compostable polymer films (biodegradable copolyester films) of 20 microns to 30 microns were produced with up to 20% polyhalite with uniform results.
[0267] -Polyhalite + KCl:
[0268] Compostable polymer films (biodegradable copolyester films) of 20-30 microns were produced with up to 10% polyhalite + KCl with uniform results.
[0269]
[0270] Table 14
[0271] *Reference - Biodegradable copolyester cover with 0% PH
[0272] **PH-polyhalite
[0273] From Table 14, it can be seen that in addition to the favorable benefits of adding polyhalite or polyhalite and KCl to the mulch in terms of faster biodegradability, it can also be seen that such addition can also affect the tensile strength, elongation and tear resistance of the mulch.
[0274] According to some embodiments, the addition of polyhalite alone or polyhalite and KCl (50 / 50) at a concentration of 10% may also have benefits in terms of elongation, making the covering more flexible.
[0275] It will be appreciated that, for the sake of clarity, the various features of the present invention described in the context of a separate embodiment may also be provided in combination in a single embodiment. On the contrary, for the sake of brevity, the various features of the present invention described in the context of a single embodiment may also be provided individually or in any suitable sub-combination. It will also be appreciated by those skilled in the art that the present invention is not limited by what has been particularly shown and described above.
Claims
1. A mulch film composition comprising a sulphate mineral in a concentration between 1% w / w and 50% w / w of the composition.
2. The composition according to claim 1, wherein the sulfate mineral is selected from the group consisting of anhydrite, gypsum, kieserite, epsomite, glauberite, leonite, leonite, philadelphite, sylvite, leonite, polyhalite or a combination thereof.
3. The composition of claim 2, wherein the sulfate mineral is polyhalite.
4. The composition according to claim 3, wherein the film has a thickness of 10 mm to 150 mm.
5. The composition according to claim 4, wherein the film has a thickness of 10 mm to 30 mm.
6. A composition according to claim 5, wherein the concentration of the sulphate mineral is 10% w / w - 20% w / w of the composition.
7. The composition of claim 3 comprising a combination of polyhalite and potash.
8. The composition of claim 1, wherein the cover film comprises a biodegradable copolyester film.
9. A process for producing a covering film composition comprising mixing 50%-99% of the biodegradable copolyester film with 1%-50% of polyhalite in an extruder at a temperature of 180°C-240°C and an RPM between 600-1000; extruding the mixture of the biodegradable copolyester film and polyhalite until pellets are produced; and The pellets are transferred to a film extruder to produce a mulch film composition.
10. The process of claim 9, wherein the blanket film composition has a thickness between 7.5 microns and 40 microns.
11. The process of claim 9, wherein the extruder is an 18 mm twin screw extruder.
12. The composition of claim 1, further comprising a plasticizer, a pigment compound, a stabilizer, a flame retardant, or a reinforcing filler.
13. A method of controlling the biodegradation of a biodegradable mulch film comprising incorporating into said film at least one sulphate mineral at a concentration of from 10% w / w to 30% w / w.
14. The method of claim 13, wherein the at least one sulfate mineral is polyhalite.
15. The method of claim 14, wherein said controlling the biodegradation of said biodegradable cover film comprises slowing the degradation rate of said film to 10% to 16% per year.
Citation Information
Patent Citations
Biodegradable mulching film for slow-release fertilizer as well as preparation method and application of biodegradable mulching film
CN115926347A
Polyester biodegradation agricultural mulching film as well as preparation and application of polyester biodegradation agricultural mulching film
CN102702694A
Fully biodegradable and multi-functional plastic mulch
CN103289134A
Fully biodegradable insecticide tolerance mulching film composition and preparation method thereof
CN107955350A
Agricultural mulch film transparent composite
CN109810353A